Konflikty w przestrzeni społecznej miasta - Karwińska, Anna (Space – Society – Economy, 2009)
Cities have emerged thousands years ago as a cultural response to new expectations and aspirations of individuals and social groups. But, meeting these needs always was (and is currently) a very complex process which is often an important source of conflicts, both – spatial and social. It is worth mentioning that within cities, for centuries, there is, often acute, battle for space, for the best localization, for the prestige of the given place. These distinctions between „good” and „bad” neighborhoods are, in many cities, stable and long lasting, supported by generations. Then, one can distinguish divisions based on ethic and religious diversity within the urban space. Sometimes, they enrich city attractions, sometimes they contribute to conflict character of social and spatial relations. This is especially the case when every minority wants to stress its own cultural heritage. There are some other problems connected with the development of gated communities mirroring patterns of social inequalities and social distances existing within the city. For the majority of cities, there are characteristic phenomena of unequal access to some goods and services – so cities are often „places of frustration” generating conflicts between groups. There are also problems strengthening unmanageable conflicts between private and public interests. The development of higher level of urban governance, efficient institutions negotiating various interests and aspirations seems to be the best key to solve spatial and social conflicts within the city.